Age-related changes of human balance during quiet stance - Abrahamová, D; Hlavacka, F (Physiological research, 2008)
Certain aspects of balance control change with age, resulting in a slight postural instability. We examined healthy subjects between 20-82 years of age during the quiet stance under static conditions: at stance on a firm surface and/or on a compliant surface with eyes either open or closed. Body sway was evaluated from centre of foot pressure (CoP) positions during a 50 sec interval. The seven CoP parameters were evaluated to assess quiet stance and were analyzed in three age groups: juniors, middle-aged and seniors. The regression analysis showed evident increase of body sway over 60 years of age. We found that CoP parameters were significantly different when comparing juniors and seniors in all static conditions. The most sensitive view on postural steadiness during quiet stance was provided by CoP amplitude and velocity in AP direction and root mean square (RMS) of statokinesigram. New physiological ranges of RMS parameter in each condition for each age group of healthy subjects were determined. Our results showed that CoP data from force platform in quiet stance may indicate small balance impairment due to age. The determined physiological ranges of RMS will be useful for better distinguishing between small postural instability due to aging in contrast to pathological processes in the human postural control.
Keywords: senioři; biomechanika; propriocepce; Aging; senioři nad 80 let; Biomechanical Phenomena; Middle Aged; Postural Balance; mužské pohlaví; tlak; Pressure; Adult; mladý dospělý; věkové faktory; Aged, 80 and over; stárnutí; Proprioception; Young Adult; ženské pohlaví; Humans; lidé středního věku; Age Factors; posturální rovnováha; dospělí; Female; Aged; lidé; Male